Impact of Organic Agriculture on the Quality of Grapes (Syrah and Tempranillo) Harvested in Guanajuato, Mexico: Relationship Between Soil Elemental Profile and Grape Bioactive Properties - Fabio Macías-Gallardo; Tannia Alexandra Quiñones-Muñoz; Raúl Miranda-Avilés; Luis Felipe Ramírez-Santoyo; Gabriela Ana Zanor; César Ozuna (Agriculture)
Viticulture has migrated to organic management to reduce environmental impact. Grapes harvested in organic vineyards (ORGs) could have a better polyphenol profile than conventional vineyards (CONs). The objective was to evaluate the relationship between agricultural management, elemental soil profile, and grape bioactive compounds (var. Syrah and Tempranillo). Soil components were determined from CON and ORG vineyards; they were correlated with bioactive compounds in grape skin and seed through principal component analysis (PCA). The ORG vineyard presented higher moisture (4.50–5.72%), clay (31.70–40.55%), organic matter (OM) (9.44–11.01%), P (108.72–122.16 mg/kg), N (0.27 mg/kg), and oxides (Fe2O3, SiO2, MnO, TiO2) in soil and phenolic compounds (myricetin, quercetin, resveratrol, ellagic acid, others) and antioxidant capacity in grape skin and seed. Regarding PCA (>74.20% of variance), the first component showed positive correlations (>0.60) between pH, moisture, clay, and soil oxides (MgO, K2O, Al2O3), which favored biosynthesis in grape skin and seed phenols (catechin, gallic acid, vanillic acid, and rutin). The second component showed positive correlations between OM, silt, soil oxides, antioxidant capacity, and phenols in grape skin and seed. Finally, the edaphic conditions of the ORG vineyard allowed for one to obtain optimal grapes for winemaking due to their higher phenol content.